Crop Livestock Integration in South Sumatera Tidal Swamp Land: Potency, Constraint and Solution Alternative - ., Isbandi (Indonesian Animal Sciences Society, 2003)
Decreasing areas of fertile soil in Java due to non agriculture purposes and increasing demand for agriculture products along with increasing human population and industrial growth have led to cultivate marginals soils like tidal swamp land areas to the development of agriculture. Integrated farming system concepts involving food crops such as rice and corn with cattle or buffaloes could be applied in tidal swamp land areas of South Sumatera. They were supported by appropriate carrying capacity and planting pattern, and sufficient supply of rice and corn straws as feed. However, infrastructural constraints, such as isolated location, and inappropriate facilities, especially by transportation were found. An integration of crop and livestock that is supported by transportation through rivers connect to markets is recommended. If such effort is sucsessful, it will increase crop production and ruminant productivity, significantly. Â Key words: Tidal swamp land, carrying capacity, planting pattern, agricultural by productcs